An All‐Round Athlete on the Track of Phototheranostics: Subtly Regulating the Balance between Radiative and Nonradiative Decays for Multimodal Imaging‐Guided Synergistic Therapy. Issue 36 (21st July 2020) - Zhang, Zhijun; Xu, Wenhan; Kang, Miaomiao; Wen, Haifei; Guo, Heng; Zhang, Pengfei; Xi, Lei; Li, Kai; Wang, Lei; Wang, Dong; Tang, Ben Zhong
Abstract: Aiming to achieve versatile phototheranostics with the integrated functionalities of multiple diagnostic imaging and synergistic therapy, the optimum use of dissipated energy through both radiative and nonradiative pathways is definitely appealing, yet a significantly challenging task. To the best of the knowledge, there have been no previous reports on a single molecular species effective at affording all phototheranostic modalities including fluorescence imaging (FLI), photoacoustic imaging (PAI), photothermal imaging (PTI), photodynamic therapy (PDT), and photothermal therapy (PTT). Herein, a simple and highly powerful one‐for‐all phototheranostics based on aggregation‐induced emission (AIE)‐active fluorophores is tactfully designed and constructed. Thanks to its strong electron donor–acceptor interaction and finely modulated intramolecular motion, the AIE fluorophore‐based nanoparticles simultaneously exhibit bright near‐infrared II (NIR‐II) fluorescence emission, efficient reactive oxygen species generation, and high photothermal conversion efficiency upon NIR irradiation, indicating the actualization of a balance between radiative and nonradiative energy dissipations. Furthermore, the unprecedented performance on NIR‐II FLI‐PAI‐PTI trimodal‐imaging‐guided PDT–PTT synergistic therapy is demonstrated by the precise tumor diagnosis and complete tumor elimination outcomes. This study thus brings a new insight into the development of superior versatile phototheranostics for practical cancer theranostics. Abstract : An all‐round phototheranostic agent based on a single aggregation‐induced emission (AIE)‐active fluorophore allowing fluorescence imaging (FLI), photoacoustic imaging (PAI), photothermal imaging (PTI), photothermal therapy (PTT), and photodynamic therapy (PDT) is constructed by subtly regulating the balance between radiative and nonradiative excited‐state energy dissipations, which thus actualizes unprecedented performance on near‐infrared‐II (NIR‐II) FLI‐PAI‐PTI trimodal imaging‐guided PDT–PTT synergistic therapy.